Characteristics of SP600125 Induced Tetraploid Cells in Comparison With Diploid and Tetraploid Cells of Fish - Fan, Yunpeng; Zhang, Guangjing; Zhao, Kaiyue; Fu, Wen; Chen, Shujuan; Liu, Jinhui; Liu, Wenbin; Peng, Liangyue; Ren, Li; Liu, Shaojun; Xiao, Yamei (Frontiers in Genetics, 2021)
In our previous research, SP600125 (Anthrapyrazolone) was used to induce autotetraploid of crucian carp cells (SP4N cells), and tetraploid fry was generated from the SP4N cells by somatic cell nuclear transfer technique. However, it is still unclear about biological characteristics of the SP4N cells. In this article, the cytological characteristic and gene expression profiles of the SP4N cells are investigated in comparison with the crucian carp cells (2N cells) and the tetraploid crucian carp cells (CC4N cells). The SP4N cells have tetraploid characteristics in terms of morphology and DNA ploidy levels, and their chromosome behavior is stable during the cell proliferation. The migration ability and the mtDNA copy number of SP4N cells are both lower than those in the CC4N cells and the 2N cells, but there exist giant mitochondria in the SP4N cells. The similar expression trends in the cell cycle regulation genes of the SP4N cells and 2N cells, while the corresponding expression profiles are clearly different between the SP4N cells and the CC4N cells. Moreover, the significant difference genes are associated with energy metabolism pathways among the SP4N cells, 2N cells and CC4N cells. These results can provide deeper understanding of SP600125 induction, as well as finding applications in polyploidization breeding of fish species.